EKSPLORASI DAN KARAKTERISASI PADI LOKAL DI TAPANULI SELATAN PROPINSI SUMATERA UTARA - Mukhlis, Mukhlis (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
Research on the Exploration and Characterization of Several Local Rice Plants in South Tapanuli Regency, North Sumatra Province. The purpose of this study is to determine the level of diversity and similarity of the phenotypic character of local rice plants with the exploration and identification of morphological characters in South Tapanuli Regency. Sampling was carried out randomly (purposive sampling) from South Tapanuli Regency. The data observed are in the form of quantitative data and qualitative data of local rice plants.Â  The results of the study show that rice cultivars are found in various areas in South Tapanuli Regency with a high diversity of characteristics. From the observation results, a similarity analysis was described and carried out using the NTSYS 2.02 program. The results showed that 10 cultivars of local rice plants with a similarity coefficient of 0.29-0.92 or 29-92% were obtained. 2 genotypes were obtained that were grouped close together, namely C4 and C5 at a coefficient of 0.71. Judging from the coefficient of similarity of local rice plants in the location are close relatives.